SEKULARISASI PESANTREN (Studi Analisis atas Dinamika Kurikulum Pesantren) - Munjahid, Munjahid (IAIN Ponorogo, 2011)
It is broadly assumed that the Islamic boarding house is a conservative, static, and inclusive institution. The similar idea has been raised by Geerzt whom he classifies the members of Islamic school as conservative Muslim. In fact, this allegation seems over generalized and unfounded. This is absolutely unfair because there have been valuable rapid changes of this institution that suit on the need of global development, although the changes occur without excluding the traditional system. Moreover, the changes are getting faster and more significant after the inclusion of two main subjects, such as mantiq and ushul fiqh which might greatly adopt and concede the logic of the Greek philosophers. On the other hand, some of Muslims still show deep antipathetic attitudes towards the sciences from the West which entered into Islamic boarding schools. They argue that it will gradually shift the Islamic tradition into the secular Western tradition. They do not realize that whatever the discipline occupied, it is indeed considered as the science of Islam under condition that it provides them with science and knowledge of the truth of Allah, piety, fear to God, useful, able to bring the knowledge of Gods power (khasyyah) and for the benefit of all mankind. Thus, what some people consider as secular science, truly it belongs to the science of Islam. In other words, secularization is actually the Islamization itself.Â Ø¸Ù ÙØ«ÙØ± Ù Ù Ø§ÙØ¨Ø§ØØ«ÙÙ Ø£ÙÙ Ø¨Ø³ÙØªØ±ÙÙ Ù Ø¤Ø³Ø³Ø© ØªØ±Ø¨ÙÙØ© Ù ØªØ®ÙÙØ© ÙØ¬Ø§Ù Ø¯Ø©. ÙØ¹ÙÙ ÙØ°Ø§Ø Ø³Ù ÙÙ Ø¬ÙØªØ³ Ø£ÙÙ Ø¨Ø³ÙØªØ±ÙÙ Ø¨Ø§ÙÙ Ø³ÙÙ ÙÙ Ø§ÙÙ ØªØ®ÙÙÙÙ Ø§ÙØ¬Ø§Ù Ø¯ÙÙ. ÙØ°Ù Ø§ÙØªÙÙ Ø© ÙØ§ ØªÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³Ø ÙØ£Ù Ø§ÙØªØºÙØ±Ø§Øª ÙÙØ¹Øª ÙÙÙØ§Ø ÙÙÙÙØ§ ÙØ§ ØªÙØ¹ Ø¨Ø§ÙÙ Ø§Ù Ø§ÙÙØ¸Ø§Ù Ø§ÙØªÙÙÙØ¯Ù ÙØªØ±ÙÙØ Ø¨Ù ÙØ§ÙØª ÙØ°Ù Ø§ÙØªØºÙØ±Ø§Øª ÙØ¨ÙØ±Ø©Ø Ø®Ø§ØµØ© Ø¨Ø¹Ø¯ Ø§Ø¯Ø®Ø§Ù Ù Ø§Ø¯Ø© Ø£ØµÙÙ Ø§ÙÙÙÙ ÙØ§ÙÙ ÙØ·Ù ÙÙ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³ÙØ ÙÙÙ Ø§ Ù ÙØ±ÙØ«Ø§Ù Ù Ù Ù ÙØ·Ù Ø§ÙÙÙØ³ÙØ© Ø§ÙÙÙÙØ§ÙÙÙØ©. ÙÙØ§Ø²Ø§Ù Ø¨Ø¹Ø¶ Ø§ÙÙ Ø³ÙÙ ÙÙ Ù ØªÙÙ Ø§ Ø£Ù Ø§ÙØ¹ÙÙÙ Ø§ÙØºØ±Ø¨ÙØ© Ø§ÙØ¯Ø§Ø®ÙØ© ÙÙ Ø¨Ø³ÙØªØ±ÙÙ Ø³ÙÙ ØªØºÙÙØ± ØªØ¯Ø±ÙØ¬ÙØ§ Ø§ÙØ¹Ø§Ø¯Ø§Øª ÙØ§ÙØªÙØ§ÙÙØ¯ ÙÙ Ø¨Ø³ÙØªØ±ÙÙ Ø¥ÙÙ Ø§ÙØ¹Ø§Ø¯Ø§Øª ÙØ§ÙØªÙØ§ÙÙØ¯ Ø§ÙØºØ±Ø¨ÙØ© Ø§ÙØ¹ÙÙ Ø§ÙÙØ©. ÙÙ ÙØ§ ÙØ¹Ø±ÙÙÙ Ø£Ù ÙÙÙ Ø¹ÙÙ Ø¬Ø¹Ù Ø£ÙÙÙ Ù Ø¤Ù ÙØ§ Ø¨Ø§ÙÙÙ ÙÙ ØªÙÙÙØ§ ÙØ³Ø§Ø¹Ø¯Ù ÙÙ Ù Ø¹Ø±ÙØ© ÙØ¯Ø±Ø© Ø§ÙÙÙ ÙÙÙ Ø¥Ø³ÙØ§Ù Ù. Ø¨ÙØ°Ø§ Ø£ØµØ¨Ø Ù Ø§ ÙØ¸ÙÙÙ Ø¨Ø¹Ø¶ Ø§ÙÙØ§Ø³ Ø¹ÙÙ Ø§ÙÙÙØ§ ÙÙÙ Ø¥Ø³ÙØ§Ù ÙÙØ ÙØ§ÙØ¹ÙÙ Ø§ÙÙØ© ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙØ³ÙØ§.